What An Entrepreneurial Mindset Contributes To Increasing The Creativity Of Graduates - Muhibuddin Ahmadi; Muhammad Irfan Aprilian; Sarianti S. Pataba (International Forum of Researchers and Lecturers, 2022)
The entrepreneurial part of the program encourages graduates to think creatively, innovate, and take risks. This will help students develop the capacity to come up with innovative ideas, spot opportunities, and confront difficulties in novel ways. The goal of this research is to determine what variables hinder graduate creativity and how entrepreneurial orientation in learning might help increase graduate creativity. This study employed a qualitative technique with a library approach. Data sources were obtained via library examination of papers, journals, publications, and so on. The findings of this study show that factors inhibiting graduate creativity include an overly structured curriculum, monotonous teaching methods, and limited resources and facilities in the form of infrastructure, which are among the most significant barriers to students developing creative ideas..